Review on Anticancer Activity of Essential Metal Dithiocarbamate Complexes - Rizal Irfandi; Indah Raya; Ahyar Ahmad; Ahmad Fudholi; Hasnah Natsir; Desy Kartina; Harningsih Karim; Santi Santi; Subakir Salnus (Universitas Gadjah Mada, 2022)
The importance of essential metal ions and their metal complexes in the creation of prospective medical therapies has long been recognized. In chemistry, molecular biology, and medicinal fields; the interaction of metal complexes with DNA has been a subject of study. The dithiocarbamate essential metal complex is described extensively in the literature for its various benefits and advantages. With proper use of ligands, it is proven to increase the cytotoxic activity of metal complexes against cancer cells. Some researches have shown significant progress regarding the biological activities of the dithiocarbamate essential metal complex as antimicrobial, antioxidant, and anticancer agents. Metal complexes form complexes with dithiocarbamate ligands with unique structural variations. In this study, we presented an overview of the cytotoxic effects of some dithiocarbamate essential metal complexes on cancer cells, as well as fresh approaches to the design of essential metal-based therapeutics containing dithiocarbamate and molecular targets in cancer therapy. This review may provide an update on recent developments in the medicinal use of essential metals with dithiocarbamate ligands, carried out to identify recent relevant literature. Finally, we predict that the essential metal complexed with dithiocarbamate can be a new breakthrough in the future development of cancer drugs.